2017
DOI: 10.1155/2017/5432818
|View full text |Cite
|
Sign up to set email alerts
|

Role of ARPC2 in Human Gastric Cancer

Abstract: Gastric cancer continues to be the second most frequent cause of cancer deaths worldwide. However, the exact molecular mechanisms are still unclear. Further research to find potential targets for therapy is critical and urgent. In this study, we found that ARPC2 promoted cell proliferation and invasion in the human cancer cell line MKN-28 using a cell total number assay, MTT (3-(4,5-dimethyl-2-thiazolyl)-2,5-diphenyl-2-H-tetrazolium bromide) assay, cell colony formation assay, migration assay, invasion assay, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 44 publications
(40 reference statements)
1
21
0
Order By: Relevance
“…As reported previously, the silencing of the ARP2/3 complex decreased the migration of pancreatic cancer cells (33). Zhang et al reported that ARPC2 promoted the proliferation and invasion of the human gastric cancer cell line, MKN-28; ARPC2 exhibited a higher expression in gastric cancer tissues than in normal gastric tissues; ARPC2 was significantly associated with a large tumor size, lymph node invasion, and a high tumor stage of gastric cancer patients; ARPC2-positive patients exhibited lower RFS and OS rates compared with ARPC2-negative patients (34). These data all support our present results.…”
Section: Discussionsupporting
confidence: 91%
“…As reported previously, the silencing of the ARP2/3 complex decreased the migration of pancreatic cancer cells (33). Zhang et al reported that ARPC2 promoted the proliferation and invasion of the human gastric cancer cell line, MKN-28; ARPC2 exhibited a higher expression in gastric cancer tissues than in normal gastric tissues; ARPC2 was significantly associated with a large tumor size, lymph node invasion, and a high tumor stage of gastric cancer patients; ARPC2-positive patients exhibited lower RFS and OS rates compared with ARPC2-negative patients (34). These data all support our present results.…”
Section: Discussionsupporting
confidence: 91%
“…ARPC2 is one of the subunits of the Arp2/3 complex and is required for maintaining the structural integrity of the entire complex. ARPC2 expression is associated with metastasis and poor prognosis of patients with melanoma or gastric tumors . Recently, we reported that ARPC2 inhibitor (benproperine, Benp) suppressed the migration and invasion of cancer cells and tumor metastasis in animal models .…”
Section: Introductionmentioning
confidence: 99%
“…Among these subunits, ARPC2 (subunit 2, 34 kDa) has a fundamental role in the nucleation of actin filaments (AFs) and participates in the polarization of the Golgi apparatus (11). Al Ghouleh et al demonstrated that ARPC2 participates in smooth muscle cell migration (12), Zhang et al also reported that ARPC2 may be involved in human gastric cancer cell proliferation or migration (13). Thus ARPC2 is critical to cell migration and invasion (14).…”
Section: Introductionmentioning
confidence: 99%